1985
DOI: 10.1152/jappl.1985.59.4.1128
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-lymph exchange and interstitial distribution volumes of charged macromolecules in the lung

Abstract: The plasma-lymph exchange of two lactate dehydrogenase (LDH) isozymes (4.2 nM) of different molecular charge between plasma (CP) and lung lymph (CL), their initial clearances across the capillary wall, and their extravascular distribution volumes were studied in dog lungs at control and increased left atrial pressures (Pla = 23.3 +/- 2.1 cmH2O). The anionic LDH 1 [isoelectric point (pI) = 5.0] exhibited a more rapid plasma decay compared with cationic LDH 5 (pI = 7.9) after bolus injection but was maintained r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 0 publications
3
33
1
Order By: Relevance
“…The charge-dependence in vascular permeability in tumours is consistent with observations in normal tissues (Jain, 1997;Curry et al, 1987;Turner et al, 1983;Vehaskari et al, 1984;Deen et al, 1980;Baldwin et al, 1991;Dermietzel et al, 1983;Adamson et al, 1988;Barrowcliffe et al, 1990;Gandhi and Bell, 1992;Gilchrist and Parker, 1985;Haraldsson et al, 1983;Khaw et al, 1991;Leypoldt and Henderson, 1993;Michel and Phillips, 1985;Öjteg et al, 1987;Parker et al, 1985;Rasio and Goresky, 1985;Triguero et al, 1989), suggesting the luminal surface of tumour vascular endothelium is negatively charged as well.…”
Section: Molecular Charge-dependence Of Vascular Permeabilitysupporting
confidence: 82%
See 1 more Smart Citation
“…The charge-dependence in vascular permeability in tumours is consistent with observations in normal tissues (Jain, 1997;Curry et al, 1987;Turner et al, 1983;Vehaskari et al, 1984;Deen et al, 1980;Baldwin et al, 1991;Dermietzel et al, 1983;Adamson et al, 1988;Barrowcliffe et al, 1990;Gandhi and Bell, 1992;Gilchrist and Parker, 1985;Haraldsson et al, 1983;Khaw et al, 1991;Leypoldt and Henderson, 1993;Michel and Phillips, 1985;Öjteg et al, 1987;Parker et al, 1985;Rasio and Goresky, 1985;Triguero et al, 1989), suggesting the luminal surface of tumour vascular endothelium is negatively charged as well.…”
Section: Molecular Charge-dependence Of Vascular Permeabilitysupporting
confidence: 82%
“…Thus, it restricts the extravasation of anionic macromolecules, as has been demonstrated in cultured endothelial cell monolayer (Sahagun et al, 1990) and various normal tissues (Jain, 1997;Curry et al, 1987;Turner et al, 1983;Vehaskari et al, 1984;Deen et al, 1980;Baldwin et al, 1991;Dermietzel et al, 1983;Adamson et al, 1988;Barrowcliffe et al, 1990;Gandhi and Bell, 1992;Gilchrist and Parker, 1985;Haraldsson et al, 1983;Khaw et al, 1991;Leypoldt and Henderson, 1993;Michel and Phillips, 1985;Öjteg et al, 1987;Parker et al, 1985;Rasio and Goresky, 1985;Triguero et al, 1989). Adamson et al (1988) have demonstrated that the microvascular permeability to α-lactalbumin (M r = 14 176, net charge -10) is approximately 50% of that to ribonuclease (M r = 13 683, net charge +4), suggesting that the microvascular permeability to the positively charged molecules is higher than the permeability to the negative ones.…”
mentioning
confidence: 95%
“…Glomerular capillaries appear to clear anionic molecules more slowly than cationic molecules of very similar hydrodynamic radii (1). In contrast, in pulmonary mi-tated when compared with neutral dextran (2)(3)(4)(5). Since electron microscopic examinations have shown a distribution of anionic sites on the endothelial surface in both glomeruli and pulmonary microvessels (5-7), differences in transport of macromolecules based on molecular charge between these organs might be attributed to the charge and construction of the basement membranes and interstitium (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are mounting data suggesting that molecular filtration is also influenced by the interaction of charges on the endothelial surface with charged circulating molecules (1)(2)(3)(4). Glomerular capillaries appear to clear anionic molecules more slowly than cationic molecules of very similar hydrodynamic radii (1).…”
Section: Introductionmentioning
confidence: 99%
“…Second, when proteins are infused intravenously to experimental animals, they are readily detected in lung lymph and ELF (20,21,28,30,36). Furthermore, when a1-antitrypsin is infused intravenously to humans, the a1-antitrypsin is readily detectable in the lower respiratory tract ELF at levels -15% that achieved in plasma (37).…”
Section: Methodsmentioning
confidence: 99%